Different sources of market information and product innovativeness - Dąbrowski, Dariusz (Economics and Business Review, 2018)
The purpose of this study is to identify whether the gathering of market information from different sources – i.e. from customers, competitors and other entities – is related to product innovativeness. The relationships proposed so far have not been empirically investigated but they can have important theoretical and practical implications for product innovation. To achieve the purpose of the paper data concerning 287 new products were used by applying confirmatory factor analysis and structural equation modelling. The findings indicate that the obtaining of market information from customers and market entities, other than customers and competitors, has a positive impact on product innovativeness, but there was no such relationship in the case of gathering information from competitors.